Analysis of Pedestrian Safety Level Using Pedestrian Risk Index (PRI) for Student Pedestrians at SMAN 1 Gunung Talang - Rizky Indra Utama; Darma Hendra (Universitas Negeri Padang, 2025)
Pedestrians are the most vulnerable road users. If involved in an accident, the risk of fatality they face is greater than that of other road users (Shinar, 2007). This study aims to analyze the level of safety for pedestrians based on the level of risk expressed by the Pedestrian Risk Index (PRI). The case study was conducted on pedestrian students at SMAN 1 Gunung Talang. The data in this study are traffic conflict data obtained from analysis of field observations. The data required in calculating the Pedestrian Risk Index (PRI) were obtained from field observations. The observations were conducted over two days, namely Monday and Tuesday, where the morning survey was conducted from 06.30 - 07.30 when students entered school and in the afternoon from 15.00 - 16.00 when students returned from school. The data were further analyzed to obtain the Pedestrian Risk Index (PRI) value. The results of the data analysis show that there are differences in PRI values ​​based on the day and time of the crossing, namely crossings carried out in the morning have a higher average PRI value of 124.91 than crossings in the afternoon with an average PRI value of 61.55. Based on this study, it can be concluded that crossings carried out in the afternoon have a higher level of safety compared to crossings carried out in the morning.